History of Mathematics Education in Brazil: an overview of secondary education - Magalhaes Gomes, Maria Laura; Marafioti Garnica, Antonio Vicente [UNESP] (Univ Montana, Dept Mathematical Sciences, 2021)
The field of the history of mathematics education, inscribed in the field of research on mathematics education in Brazil, has been developed as a result of the work of many groups of researchers, dedicated to varied themes under the light of various theoretical and methodological approaches. While it is impossible to describe in detail such studies in a single article, the objective of this text is to offer an overview of research results on a specific topic - mathematics in secondary education and training of teachers to teach at this level, over the years. The current situation of the country regarding education in general is related to the past and different Brazilian political periods: Colony, Empire and Republic. We will succinctly examine the beginnings of Brazilian basic school education before the Republic, seeking to highlight characteristics of secondary school studies, especially regarding the teaching of mathematics. Then, we will focus on the same themes during the period after the establishment of the Republican regime. Finally, we will discuss the historical trajectory of the training mathematics teachers who work on secondary education in the country.
Keywords: History of mathematics education in Brazil; History of secondary education in Brazil; History of the formation and practice of mathematics teachers in Brazil